FORMAÇÃO DOCENTE NA MODALIDADE A DISTÂNCIA: ENCONTROS, AFETOS/AFECÇÕES - Moreira, Nilcea Elias Rodrigues (2020)
This study deals with the effects that emerge from experienced encounters in the formative paths for teachers in distance modality, in the relation dimension between affects/affections and learnings. It problematizes the learning, creative and inventive e